Parotidectomy under Sedation and Locoregional Anesthesia with Monitoring of Brain Activity (2017)
ABSTRACT: Background. Parotidectomy is usually performed while the patient is under general anesthesia, however, sedation with locoregional anesthesia could be an alternative. Methods: Fifteen adult patients with parotid tumors of the superficial lobe were included in this study. Anesthetic procedure consisted of sedation associated with cervical plexus and auriculotemporal nerve block. Sedation was managed based on the bispectral index. Results: Superficial parotidectomies were performed in 13 patients, and combined partial resections were performed in 2 patients. The mean operative time was 118.2 ± 16.4 minutes. Conversion to general anesthesia was necessary in only 1 patient. Ten surgeries were performed on an outpatient basis. Definitive facial paralysis occurred in 1 patient. All patients reported total satisfaction with the procedure. Conclusion: In selected cases, parotidectomy under sedation plus locoregional anesthesia is feasible and safe. The careful selection of patients and the close collaboration with an anesthesiologist is the key to a successful procedure.